MANAJEMEN PROGRAM PEMBIASAAN RELIGIUS DALAM MEMBENTUK KARAKTER INTEGRITAS SISWA - Suherman, Maman; Mastiani, Emay; Fitrianingsih; Setiaji, Dini Anggraeni Saputri; Nasruloh, Ujang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the management of a religious habituation program in shaping the character integrity of students at SDN Sukamanah, Bandung Regency. This study uses a qualitative approach with a case study method. Data collection was conducted through interviews, observations, and documentation studies. Data analysis was conducted descriptively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the management of the religious habituation program is carried out through the stages of planning, organizing, implementing, monitoring, and evaluating. In the planning stage, the school sets character building goals, analyzes students' needs and characteristics, and designs religious habituation activities integrated into school activities. Organization is carried out through a clear division of roles and responsibilities between the principal and teachers in a collaborative manner. This program is implemented routinely and continuously through various religious activities supported by teacher role models and active student participation. Monitoring and evaluation are carried out continuously through observation of student behavior with an emphasis on guidance and continuous improvement. Challenges faced include limited time, differences in student backgrounds, and a lack of continuity in the religious education program between the school and families. Efforts made by the school include strengthening teacher commitment, implementing a personal approach to students, and increasing collaboration with parents. Overall, the management of the religious habituation program provides a positive contribution in consistently forming the character and integrity of students, which is integrated into the school culture.